New records of sea anemones (Cnidaria, Anthozoa, Actiniaria) from El Salvador, Eastern Pacific - Adriana Ramírez-Orellana; Johanna Segovia; Fabián H. Acuña; Agustín Garese; Ricardo González-Muñoz (Check List, 2024)
We report the ﬁrst records of the sea anemones Anthopleura mariscali, Anthopleura nigrescens, and Exaiptasia diaphana in the Protected Natural Area of Los Cóbanos and Punta Amapala on the coast of El Salvador. Additionally, we extend the known range of distribution of Telmatactis panamensis to south-eastern El Salvador. Each of these species is brieﬂy described, and images of live specimens are provided. The geographic distributions of previous records of sea anemones in El Salvador are discussed. An updated list of 11 species reported in the country is provided.